Possible IgG4-related respiratory disease (IgG4-RRD) - a rare presentation as a Pancoast tumour-like - Pereira, Inês S.; Fonseca, Diogo; Dias, Margarida; Barroso, Ana; Pinto, Patrícia; Machado, Daniela (Brazilian Journal of Case Reports, 2021)
IgG4-related respiratory disease (IgG4-RRD) is a recently recognized disease that can have multiple presentations. In many cases, the exclusion of malignancy is essential. We present a case of a male patient with right omalgia and supraclavicular swelling. Radiologic exams showed a lung mass suggestive of a Pancoast tumour in the right upper lobe. Patient underwent transthoracic biopsies that revealed fibromuscular tissue with fibrosis, lymphoplasmacytic infiltrate and a significant increase in IgG4 cells with 15% IgG4/IgG ratio. He started on prednisolone with clinical and radiologic improvement. As it is a heterogeneous disease it is important that clinicians are aware of the possible presentations.